2017
DOI: 10.3847/1538-3881/aa88be
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Near-Earth Asteroids Using KMTNET-SAAO

Abstract: We present here VRI spectrophotometry of 39 near-Earth asteroids (NEAs) observed with the Sutherland, South Africa, node of the Korea Microlensing Telescope Network (KMTNet). Of the 39 NEAs, 19 were targeted, but because of KMTNet's large 2 deg × 2 deg field of view, 20 serendipitous NEAs were also captured in the observing fields.Targeted observations were performed within 44 days (median: 16 days, min: 4 days) of each NEA's discovery date. Our broadband spectrophotometry is reliable enough to distinguish amo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Together, these two asteroid types represent ∼ 90% of our sample, with the rest likely to be Q-and X-type asteroids. This compositional fraction is in agreement with the results of our previous publications (Mommert et al 2016;Erasmus et al 2017) which are based on UKIRT and KMTNet-SAAO observations.…”
Section: Conclusion and Future Outlooksupporting
confidence: 93%
See 1 more Smart Citation
“…Together, these two asteroid types represent ∼ 90% of our sample, with the rest likely to be Q-and X-type asteroids. This compositional fraction is in agreement with the results of our previous publications (Mommert et al 2016;Erasmus et al 2017) which are based on UKIRT and KMTNet-SAAO observations.…”
Section: Conclusion and Future Outlooksupporting
confidence: 93%
“…Perna et al (2018), for a sample of 146 objects, found an S fraction of ∼ 40%. Our team, using different telescopes and samples than the one presented in this paper, found ∼ 40% with 40 NEOs in Mommert et al (2016), while Erasmus et al (2017), with a sample of 45 objects, obtained an S fraction of ∼ 43%. Using a sample of 252 objects Stuart & Binzel Figure 8.…”
Section: Limitations and Comparison With Previous Studiesmentioning
confidence: 47%
“…Krugly et al 2002;Chang et al 2015), spectrophotometry (e.g. Mommert et al 2016;Erasmus et al 2017;Navarro-Meza et al 2019), spectroscopy (e.g Binzel et al 2004Binzel et al , 2019, radar techniques (e.g. Ostro et al 2006), andpolarimetry (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their relative proximity to the Earth, the motion of Solar System objects is key to their discovery. ML and AI have enabled removal, or reduction, of false detections from the moving object detection pipeline in the Subaru/Hyper‐Suprime‐Cam Strategic Survey Program (Lin et al, ), with applications to Trans‐Neptunian Objects (Chen et al, ); and detection and classification of asteroids (Erasmus et al, , ; Smirnov & Markov, ). Duev et al () trained a CNN to discover fast‐moving candidates from ZTF observations in order to more reliably identify potentially hazardous near‐Earth objects. Active galactic nuclei and quasars .…”
Section: Assessing the Maturity Of Adoptionmentioning
confidence: 99%